Connections between Asian and European World Cities: Measurement, Analysis, and Evaluation - Ben Derudder; Xiang Feng; Wei Shen; Rui Shao; Peter J. Taylor (Land, 2022)
Although world regions continue to be a key feature of the geographical imagination, there has been relatively little innovative research on world regionalization through the lens of city connections. Against the backdrop of an increasingly urban and interconnected world, in this paper, we evaluate the connections between European and Asian world cities. Based on a model conjecturing intercity connections through office locations of globalized producer services firms, we analyze the networks of both regions’ major cities. To this end, we establish frameworks that allow (1) comparison of the level of connectivity of cities and (2) analysis of the strength and orientation of the interactions between cities. We find that both Europe and Asia have a larger number of well-connected cities than any other world region. Both regions are roughly comparable in terms of the distribution of their urban connectivities, but there are some notable differences (e.g., Asia’s system being more top-heavy) and evolutions (e.g., Asian cities gaining more connectivity over the last decade). There are also two geographical dimensions to the interpretations of these patterns of urban connectivity: (1) the variegated importance of state-spaces (e.g., national gateways) and (2) the uneven regional focus of intercity connections (e.g., Luxembourg and Singapore being less dependent on regional connections). We use our findings to argue that the time is ripe for a more nuanced and contextualized answer to the question of how cities (can) act politically on the global scale in general and Asia–Europe relations in particular.